Creating wheelchair-controlled video games: Challenges and opportunities when involving young people with mobility impairments and game design experts. Issue 94 (October 2016) - Gerling, Kathrin M.; Linehan, Conor; Kirman, Ben; Kalyn, Michael R.; Evans, Adam B.; Hicks, Kieran C.
Abstract: Although participatory design (PD) is currently the most acceptable and respectful process we have for designing technology, recent discussions suggest that there may be two barriers to the successful application of PD to the design of digital games: First, the involvement of audiences with special needs can introduce new practical and ethical challenges to the design process. Second, the use of non-experts in game design roles has been criticised in that participants lack skills necessary to create games of appropriate quality. To explore how domain knowledge and user involvement influence game design, we present results from two projects that addressed the creation of movement-based wheelchair-controlled video games from different perspectives. The first project was carried out together with a local school that provides education for young people with special needs, where we invited students who use wheelchairs to take part in design sessions. The second project involved university students on a game development course, who do not use wheelchairs, taking on the role of expert designers. They were asked to design concepts for wheelchair-controlled games as part of a final-year course on game design. Our results show that concepts developed by both groups were generally suitable examples of wheelchair-controlled motion-based video games, but we observed differences regarding level of detail of game concepts, and ideas of disability. Additionally, our results show that the design exercise exposed vulnerabilities in both groups, outlining that the risk of practical and emotional vulnerability needs to be considered when working with the target audience as well as expert designers. Highlights: First participatory study designing games for young people using wheelchairs. Reflection on relative contribution of game design expertise and experience. Explores representation of mobility disability by participants in design process. Reflection on how vulnerability of participants exposed through design process.